1987
DOI: 10.1164/ajrccm/136.4.947
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplasia and Immaturity of the Terminal Lung Unit (Acinus) in Congenital Diaphragmatic Hernia

Abstract: We assessed the maturity of the lungs and the radial count in 10 infants with congenital diaphragmatic hernia who died in the immediate perinatal period. The lungs were all immature, with a histologic appearance of less than stated gestational age. The ipsilateral lungs were less mature in appearance than were the contralateral ones. The radial count, an assessment of acinar complexity, was reduced in all cases, and once again the ipsilateral lung was more affected. We present evidence that, in 4 of 6 lungs, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
68
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(74 citation statements)
references
References 10 publications
4
68
2
Order By: Relevance
“…Nitrofen Fed respond to glucocorticoid because their lungs reflect the biochemical and morphologic patterns characteristic of prematurity (9,10,13) and fall within the well-known window of responsiveness to glucocorticoid therapy. Although glucocorticoid therapy in this study inhibited both somatic and pulmonary growth, long-term follow-up in other studies of both animals (43) and human beings (44.…”
Section: Olive Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrofen Fed respond to glucocorticoid because their lungs reflect the biochemical and morphologic patterns characteristic of prematurity (9,10,13) and fall within the well-known window of responsiveness to glucocorticoid therapy. Although glucocorticoid therapy in this study inhibited both somatic and pulmonary growth, long-term follow-up in other studies of both animals (43) and human beings (44.…”
Section: Olive Oilmentioning
confidence: 99%
“…George 1.f nl. (13) documented that lungs from 10 neonates dying of CDH (seven of them full term) were morphologically immature for their gestational age.…”
mentioning
confidence: 99%
“…1 The combination of pathophysiologic derangements associated with CDH, including lung hypoplasia, lung dysmaturity and pulmonary hypertension (PPHN), requires a multidisciplinary approach to care. 2,3 The complex nature of clinical management and the relatively infrequent presentation of infants with this rare malformation to single centers has lead to difficulty identifying consistent strategies for CDH management. A recent report from the Canadian Neonatal Research Network indicates better than predicted survival in Network centers, with significant improvement in the higher mortality odds strata, and 90% survival in the three centers that cared for at least 12 infants over a 22-month period.…”
mentioning
confidence: 99%
“…Despite many advances in neonatal care, CDH often remains refractory to diverse medical interventions, such as inhaled nitric oxide (NO) therapy, and persists as a common indication for extracorporeal membrane oxygenation therapy (1). Although many factors contribute to survival of infants with CDH, the overall severity of CDH is largely due to an underlying disruption of normal lung growth and development, which leads to striking decreases in airway branches, alveolarization, and vascular growth and development (20,40). Recent studies have suggested a potential genetic basis for CDH in some cases, but mechanisms that contribute to impaired lung growth in CDH remain poorly understood (4,5).…”
mentioning
confidence: 99%